Natural convection of Al2O3/H2O nanofluid in an open inclined cavity with a heat-generating element - Miroshnichenko, Igor V.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2018)
Free convection of alumina-water nanofluid in a tilted open cavity with a heat-generating solid element has been studied. The considered topic allows understanding an opportunity of nanofluids for cooling of the heat-generating elements in open cavities. Upper border is supposed to be open where nanofluid penetrates into the cavity. Simulation has been performed using the Oberbeck-Boussinesq equations formulated in non-dimensional stream function, vorticity and temperature. Finite difference method of the second order accuracy has been applied. The effects of cavity inclination angle (0 <= gamma <= pi/2), heater location (0.1 <= 8 <= 0.7, where delta is the dimensionless distance between the heater and left wall) and nanoparlicles volume fraction (0 <= phi <= 0.04) have been analyzed. It has been found that the considered parameters allow minimizing average heater temperature. The cavity inclination angle of pi/3 characterizes the heat transfer enhancement (average Nusselt number has the maximum value), while the heater average temperature has the minimum value. At the same time, a proximity of the heater to the cavity wall characterizes non-essential cooling of the heat-generating element. The most effective cooling of the heat-generating element occurs for central heater location with cavity inclination angle of pi/3. The considered alumina-water nanoparticles do not allow to intensify the cooling process for the heater element. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Nanofluid; Heat-generating source; Open inclined cavity; Finite difference method